THE IMPLEMENTATION OF AUDIO-VISUAL MEDIA TO IMPROVE MOTIVATION IN SPEAKING ENGLISH AT ELEVENTH GRADE STUDENTS (Classroom Action Research at SMAN 4 Palembang) - Hariani, Dian; Rositasari, Tri; Saraswaty, Dwi Rara (English Community Journal, 2018)
The objective of this study was to find out the implementation of audio-visual media to improve students’ motivation in speaking English. The writer has conducted a Classroom Action Research. The subjects of this study were 31 students who belong to the XI IPA 1 class. This study used classroom action research in three cycles; the planning, acting, observing, and reflecting. The score of speaking from cycle to cycle improved, the first students’ speaking performance result was the second result was, and the third was. Based on those score (from 1st cycle to 3rd cycle), showed how the implementation of audio-visual media that could be improved students’ motivation to speak English.